2015
DOI: 10.1007/s10753-015-0200-7
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside Mitigates Sepsis-Induced Myocarditis in Rats by Regulating IGF-1/PI3K/Akt/GSK-3β Signaling

Abstract: Sepsis-induced myocardial injury (SIMI) is caused by various mechanisms. The aim of this study was to investigate the effects of salidroside (Sal) on SIMI and its mechanisms in rats. The sepsis model was established by intraperitoneal injection of lipopolysaccharide (LPS) (15 mg/kg in sterile saline). Sal decreased the serum levels of creatine kinase (CK), lactate dehydrogenase (LDH), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and interleukin-1β (IL-1β), whereas the expressions of insulin-like grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…Previous research proved that the elevated levels of inflammatory markers were associated with myocardial ischemia [24]. The inflammatory stresses induced by ISO were indicated by serum IL-6, IL-1β and TNF-α elevations [25].…”
Section: Discussionmentioning
confidence: 96%
“…Previous research proved that the elevated levels of inflammatory markers were associated with myocardial ischemia [24]. The inflammatory stresses induced by ISO were indicated by serum IL-6, IL-1β and TNF-α elevations [25].…”
Section: Discussionmentioning
confidence: 96%
“…I/R increases the local or systemic release of proinflammatory cytokines, including TNF-α, IL-1β and IL-6, and further increases cardiac injury, and inhibition of the I/R-induced inflammatory response alleviates myocardial I/R injury (45,46). It has been previously hypothesized that salidroside may exhibit a protective effect on myocardial injury by inhibiting the inflammatory response (11,14,47). In vitro and in vivo experiments have demonstrated that miR-21 regulated the production of various important pro-inflammatory cytokines secreted during I/R injury (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with heart injury have increased levels of cardiac marker enzymes in serum, which are often measured as indicators of heart disease in the clinic. CK and LDH are cardiac marker enzymes, which play a pivotal role in energy metabolism and membrane permeability in the heart (He et al, 2015). Previous studies have indicated that LPS can induce heart injury, which is characterized by the elevation of CK and LDH in serum.…”
Section: Discussionmentioning
confidence: 99%